2014
DOI: 10.1371/journal.pone.0084150
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Molecular Markers for Prognosis Estimation of Acute Myeloid Leukemia: Over-Expression of PDCD7, FIS1 and Ang2 May Indicate Poor Prognosis in Pretreatment Patients with Acute Myeloid Leukemia

Abstract: Numerous factors impact on the prognosis of acute myeloid leukemia (AML), among which molecular genetic abnormalities are developed increasingly, however, accurate prediction for newly diagnosed AML patients remains unsatisfied. For further improving the prognosis evaluation system, we investigated the transcripts levels of PDCD7, FIS1, FAM3A, CA6, APP, KLRF1, ATCAY, GGT5 and Ang2 in 97 AML patients and 30 non-malignant controls, and validated using the published microarray data from 225 cytogenetically normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…Furthermore, our results supports the evidence of excessive levels of FIS 1 as a molecular marker of myeloid leukemia 45 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, our results supports the evidence of excessive levels of FIS 1 as a molecular marker of myeloid leukemia 45 .…”
Section: Discussionsupporting
confidence: 89%
“…Excessive mitochondrial fission has been associated with a decreased mitochondrial function and increased ROS 41,42 . FIS1 up-regulation decreased cellular ATP levels in anoxic cardiomyocytes and impaired glucose-stimulated insulin secretion in INS-1E cells 43,44 ; and it has been identified as a molecular marker for poor prognosis in patients with acute myeloid leukemia 45 . We observed that erythroid differentiation under FIS1 overexpression was arrested mainly at the proerythroblast level with mitochondria featuring reduced complex II and IV protein expression and membrane potential; and an immature phenotype i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse PDCD7 was rst identi ed using the screening approach in 1999 and characterized as an apoptosis-related protein that involves in apoptotic cell death of T-cells [29]. However, the speci c function of PDCD7 in human is still unknown, although several studies have reported that human PDCD7 may related to the acute myeloid leukemia (AML) [30,31]. Compared with the non-malignant samples, higher PDCD7 expression was found in AML patients and related to lower complete remission rate, shorter relapse-free survival, and overall survival, suggesting that overexpression of PDCD7 may serve as a molecular marker for prognosis estimation of AML [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that, FIS1 , known to play important roles in apoptosis and mitochondrial fission, was shown to significantly increase across the disease sequence and this change was only seen in the Barrett’s tissue compared to matched surrounding mucosa. FIS1 is a novel gene target associated with poor prognosis in pre-treatment patients with acute myeloid leukemia [ 24 ]. Conversely, it is also upregulated in patients with non-metastatic prostate cancer [ 25 ] and plays a role in cisplatin resistance in tongue squamous cell carcinoma with cisplatin sensitivity being restored upon knockdown of FIS1 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%